2021
DOI: 10.1016/j.jiac.2021.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Early favipiravir treatment was associated with early defervescence in non-severe COVID-19 patients

Abstract: Introduction The antiviral drug favipiravir has been shown to have in vitro antiviral activity against severe-acute-respiratory-syndrome-coronavirus-2 (SARS-CoV-2). In this study, we investigated the clinical benefits and initiation of favipiravir treatment in patients with non-severe coronavirus-disease-2019 (COVID-19). Methods This study was a single-center retrospective cohort study. Receiver operating characteristic curves were drawn to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Sawanpanyalert et al (2021) demonstrated that the 140 Thai patients admitted and treated with FPV within 4 days upon symptomatic onset, in conjunction to other treatment modalities, had significantly lower odds of experiencing poor outcomes compared to those initiated treatment after 4 days of onset. Similarly, other studies also showed that early treatment, particularly by 4 days of onset, was associated with earlier defervescence [8,45]. These reports highlight the importance of early intervention and its clinical benefits, as observed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Sawanpanyalert et al (2021) demonstrated that the 140 Thai patients admitted and treated with FPV within 4 days upon symptomatic onset, in conjunction to other treatment modalities, had significantly lower odds of experiencing poor outcomes compared to those initiated treatment after 4 days of onset. Similarly, other studies also showed that early treatment, particularly by 4 days of onset, was associated with earlier defervescence [8,45]. These reports highlight the importance of early intervention and its clinical benefits, as observed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The limitation of our study is that the administration of Eba or Lor significantly reduced SARS-CoV-2-induced inflammation and lung injury, but showed limitation in suppressing viral replication in lungs of ACE2 humanized mice. A combination of MC stabilizers with antiviral drugs such as the RNA polymerase inhibitors Remdesivir and Favipiravir 6,7880 , may provide more optimal treatment strategy that dampening inflammation and clearing viruses at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…At present, antiviral drugs, such as areplivir and favipiravir, are being used in trials. The days from the onset of fever to defervescence were shown to be positively correlated with the duration from the onset of fever to the initiation of favipiravir treatment ( 35 ). However, no specific antiviral drugs have been approved for the treatment of COVID-19 ( 36 ).…”
Section: Discussionmentioning
confidence: 99%